Tackling somatic DNA contamination in sperm epigenetic studies - Kumari, Anamika; Singh, Rajender (Frontiers in Reproductive Health, 2025)
IntroductionRecent interest in sperm epigenetics has stemmed from its implication in sperm DNA quality, sperm fertility, environmental toxicity, and transgenerational inheritance. Sperm epigenetic data may be significantly affected by somatic DNA contamination, resulting in misleading conclusions. However, detecting and dealing with somatic DNA contamination in semen samples can be a challenging task.MethodsIn the present study, we worked out a detailed and robust plan to deal with somatic cell DNA contamination in sperm epigenetic studies in order to draw error-free scientific conclusions. Apart from incorporating simple quality checks, such as microscopic examination and somatic cell lysis buffer (SCLB) treatment, we compared the Infinium Human Methylation 450K BeadChip data for sperm and blood samples to identify the CpG sites that were highly methylated in blood samples in comparison to sperm, but were unrelated to infertility.Results and discussionThe comparison of Infinium Human Methylation 450K BeadChip data for sperm and blood samples identified 9564 CpG sites that can be used as markers for analyzing somatic DNA contamination. We have put together a comprehensive plan including evaluation under a microscope, SCLB treatment, inclusion of CpG biomarkers for sample quality evaluation, and applying a 15% cut off at the time of data analysis to completely eliminate the influence of somatic DNA contamination in sperm epigenetic studies. We conclude that if this comprehensive plan is followed, the influence of somatic DNA contamination in sperm epigenetic studies can be completely eliminated.